Effects of oral administratiton of elllagic acid, rich pomegranate extract on ultraviolet, induced pigmentation in the human skin - Kouichi Kasai (2006)
Effects of oral administratiton of elllagic acid, rich pomegranate extract on ultraviolet, induced pigmentation in the human skin